Bird strike : an experimental, theoretical and numerical investigation - Hedayati, Reza; Sadighi, Mojtaba (Woodhead Publishing in mechanical engineering., 2016)
Bird strikes are one of the most dangerous threats to civil and military flight safety: between 1960 and 2014, they were responsible for the destruction of approximately 150 civil aircraft and the deaths of 271 people. Bird Strike presents a summary of the damage imposed on the aviation industries by their avian counterparts. This book first presents and analyzes the statistics obtained from bird strike databases and offers various methods for minimizing the overall probability of bird-strike events. The next chapters explore how to analyze the ability of aero-engine critical structures to withstand bird-strike events by implementing reliable experimental, theoretical, and numerical methods. Finally, the book investigates the impact of bird strikes on different components of aircrafts, such as the metal fuselage, composite fuselage, engines, wings, and tail, and proposes two new bird models, with explanations of their use.